PROPRIEDADES REOLÓGICAS, TÉRMICAS E MECÂNICAS DE MISTURAS DE CELULOSE BACTERIANA E POLIPROPILENO - Frankievicz, Raysa (2014)
Due to environments problems caused by synthetic plastic, there is currently a search for replacing these materials with biodegradable materials. The study related to composites and nanocomposites formed from biodegradable materials and synthetic matrices has increased last years, and it has shown that these materials are very promising respect to biodegradation processes, besides presenting better properties than their pure components. In this work, it has been emphasized the production of nanofibers bacterial cellulose composite in a polypropylene matrix. The production of nanofibers from bacterial cellulose (BC) has been made in colloid mill. The material has been processed in a twin screw extruder in proportions of 1 %, 3% and 5% (w/w) of bacterial cellulose and coupling agent has been used as graphitized PP with maleic anhydride. The samples have been characterized by thermogravimetric analysis (TGA), x-ray diffraction (XRD), rheological characterization, infrared spectroscopy (FTIR), colorimetry, scanning electron microscopy (SEM), and tensile strength and impact. The TGA results have shown a single stage of mass loss for all samples, and thermal stability increase with filler concentration increase, which can be associated with the fiber-matrix interactions. In the XRD results, the PP has showed only the α phase remaining in the samples containing CB. In the rheological analysis, the complex viscosity has been maintained for samples containing 1% and 3% CB and pure PP, decreasing only for the 5% CB. In additional, It has been observed an enlargement of the molar mass distribution through a tendency reduction in the intersection point of G' and G". In the tensile strength, the elastic modulus has not undergone significant changes, the yield stress has decreased according to the load increasing, however it there have been significant changes with the load concentration increment. The impact strength has decreased for all samples with CB compared to pure PP. The microscopy has showed a good adhesion between fiber and matrix with bacterial cellulose clusters formation. By colorimetry process, it has been found caramelization of bacterial cellulose during the process of extrusion and injection, which causes browning of the samples.